Introduction to the Special Issue of the 55th Anniversary of Urban and Regional Planning Education: Inclusive Urban Development in the Decentralization Era - Elkana Catur Hardiansah (The Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
[Tanpa Abstrak]. Ini adalah pengantar Edisi Khusus